THE EVALUASI PENERAPAN SISTEM MANAJEMEN MUTU ISO 9001 : 2015 DI PPEI - Sri Rahayu (Politeknik STIA LAN Makassar, 2021)
Improvement in training quality is determined by many factors. One of them is the effects of training implementation management on producing good training. In order to improve the quality of training and always meet customer satisfaction and stakeholders, Indonesia Export Training Center (IETC) has implemented a quality management system with the achievement of ISO 9001 Quality Management System certification since 2004. The Quality Management System was first introduced by the International Organization for Standardization (ISO) which has been adopted in Indonesia through the National Standardization Agency of Indonesia currently as SNI ISO 9001: 2015. It is one of the reference standards for organizations. Through the implementation of a quality management system, it is believed that the management of goods or services produced by an organization comes from fulfilling customer quality requirements. The purpose of this study is to evaluate the implementation of Quality Management System ISO 9001 in IETC. The research methodology used is observation, interviews and documentation study. The results showed that the measurement of the clause analysis on the fulfillment of the requirements of Quality Management System 9001: 2015, for clauses 4 and 5 is 95% and 86.67%. This shows that the implementation of clauses 4 and 5 in IETC is in accordance with the standard requirements. Meanwhile, for clauses 6, 7, 8, 9 and 10 is 70% - 80%. Therefore, a quality management system and documentation exist; also well organized. However, the implementation of clauses 6, 7, 8, 9 and 10 has not been carried out fully.